2022
DOI: 10.3390/ijerph191912535
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal of the Coupling Relationship between Ecosystem Services and Human Well-Being in Guanzhong Plain Urban Agglomeration

Abstract: Understanding the complex relationship between ecosystem services and human well-being during the rapid development of urban agglomerations can promote the sustainable development of urban agglomerations. In this paper, the InVEST model and ArcGIS10.2 were used to analyze the spatial and temporal evolution characteristics of ecosystem services and human well-being in the Guanzhong Plain urban agglomeration. On this basis, the coupling coordination index is used to reveal the spatiotemporal coupling relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…For example, FVC showed a broader range in HH areas (0.207 to 0.959), while in PSZ areas, this range is narrowed to 0.467 to 0.548 (Table 5), with RD and NDWI showing similar trends. Current environmental models [79][80][81] commonly used for simulation and prediction, such as the InVEST model, SWAT model, and MaxEnt model, are likely to benefit from precise urban and environmental indicator ranges. By incorporating more accurate indicator data, the predictive accuracy and reliability of these models can be enhanced, thus providing a more scientific basis for urban planning and natural resource management.…”
Section: Es Synergies Within Cities In the Context Of Fragmentationmentioning
confidence: 99%
“…For example, FVC showed a broader range in HH areas (0.207 to 0.959), while in PSZ areas, this range is narrowed to 0.467 to 0.548 (Table 5), with RD and NDWI showing similar trends. Current environmental models [79][80][81] commonly used for simulation and prediction, such as the InVEST model, SWAT model, and MaxEnt model, are likely to benefit from precise urban and environmental indicator ranges. By incorporating more accurate indicator data, the predictive accuracy and reliability of these models can be enhanced, thus providing a more scientific basis for urban planning and natural resource management.…”
Section: Es Synergies Within Cities In the Context Of Fragmentationmentioning
confidence: 99%
“…Most studies have shown that ecosystem services offer many benefits to human wellbeing [69,70]. In the "grain-grain" transformation, economic production services have directly or indirectly impacted on four dimensions of well-being.…”
Section: The Relationship Between Ecosystem Services and Human Well-b...mentioning
confidence: 99%
“…Amidst global climate change, the depletion of surface water sources and decline in water quality pose significant challenges. Consequently, the spatial quantification and visual assessment of regional water yield (WY) have become focal points in contemporary ecological research and related fields [1][2][3][4]. The WY service of the basin shows considerable spatial and temporal (ST) differences, and its fluctuations influence the plant cover, climate, and soil regime directly.…”
Section: Introductionmentioning
confidence: 99%